Role-Playing Therapy in Handling Hyperactive Children - Abu Hasan Agus R; Muhammad Mushfi El Iq Bali; Izzatul Maula (Al-Hayat: Journal of Islamic Education, 2022)
This study aims to determine the results of the attitude of hyperactive children through the method of role-playing in the classroom. Children with hyperactivity disorder are very annoying to their friends in class. This hyperactive child's behaviour is complicated to regulate, primarily when learning occurs. This hyperactive child often causes trouble, disturbs his friends, paces in class, rarely does assignments, is spoiled, and screams as he likes. The method used is qualitative research with observation techniques, interview techniques, and documentation. The subjects studied were several students who behaved hyperactively in a class with many 20 students from group B. This research took place at RA Masyitoh VII Pandean, Paiton District, Probolinggo Regency. The research begins with the planning stage, implementation of research in the field, and research reports. This study indicates that the behaviour of hyperactive students often annoys other friends, do not want to be regulated, often go back and forth in class, usually leave class when learning begins, rarely do assignments, and are spoiled. Teach children to learn while playing in class. Because playing is a child's world, every child is happy to do this activity. One of the play activities that children often do is role-playing.